Improved lithium-ion secondary battery

JP7646012B2Active Publication Date: 2025-03-14レッドフォードライアン +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023544184
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-09-29
Filing Date
2021-09-28
Publication Date
2025-03-14
Estimated Expiration
2041-09-28

AI Technical Summary

Benefits of technology

【0013】 本開示のさらなる構成および利点は、添付の図面と併せて読めば、以下の詳細な説明から分かるであろう。図中、同様の数字は同様の部分を表す。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007646012000001
    Figure 0007646012000001
  • Figure 0007646012000002
    Figure 0007646012000002
  • Figure 0007646012000003
    Figure 0007646012000003
Patent Text Reader

Abstract

The lithium-ion battery includes a cathode electrode, an anode electrode formed of a porous silicon substrate having at least a portion of the surfaces of the pores of the porous silicon substrate coated with a metal silicide, a separator element disposed between the cathode and the anode, and an electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The demand for high capacity secondary batteries is strong and is increasing year by year. Many applications, such as aerospace, medical devices, portable electronics, and automotive, require cells with high gravimetric and / or volumetric capacity. Lithium-ion electrode technology can bring about significant improvements in this area. However, the theoretical specific energy density of lithium-ion cells using graphite electrodes is currently only 372 mAh / g. [Background technology]

[0002] The high electrochemical capacity of silicon makes it an attractive active electrode for use in lithium-ion battery materials. The theoretical capacity of silicon is about 4200 mAh / g, which is about 100% of the Li 4.4 This corresponds to the Si phase. However, silicon is not widely used in commercial lithium-ion secondary batteries. One of the reasons for this is that silicon undergoes large volume changes during charge-discharge cycling. For example, silicon can expand by 400% when charged to its theoretical capacity. Volume changes of this magnitude can cause significant stress on the active material structure, leading to fracture, pulverization, loss of electrical and mechanical connections within the electrode, and capacity loss.

[0003] Prior art lithium ion secondary battery electrodes typically include a polymer binder used to hold the active material on the carbon or graphite substrate. However, many polymer binders are not elastic enough to accommodate the large expansion of some high capacity materials. As a result, the particles of the active material tend to separate from each other and from the current collector. Overall, there is a need for improved utilization of high capacity active materials in lithium ion secondary battery electrodes that minimizes the above-mentioned drawbacks. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] U.S. Patent No. 8,257,866 [Patent Document 2] U.S. Patent No. 8,450,012 [Non-patent literature]

[0005] [Non-Patent Document 1] Santos et al., Electrochemically Engineered Nanoporous Material, Springer Series in Materials Science 220 (2015), Chapter 1 Summary of the Invention [Problem to be solved by the invention]

[0006] US Pat. No. 5,399,633 and US Pat. No. 5,499,666 propose to address the elasticity and expansion problems of prior art lithium-ion secondary battery electrode materials by providing an electrochemically active electrode material comprising a high surface area template containing a metal silicide and a layer of high capacity active material deposited on the template. The template is said to act as a mechanical support for the active material and / or as an electrical conductor between the active material and, for example, a substrate. According to the inventors, due to the high surface area of ​​the template, even a thin layer of active material can provide sufficient active material per surface area and obtain a corresponding electrode capacity. Thus, in theory, the thickness of the active material layer can be kept thin enough to be below its spallation threshold and maintain its structural integrity during battery cycling. The thickness and / or composition of the active material layer can also be characterized in detail to reduce expansion near the substrate interface and maintain interfacial connection. [Means for solving the problem]

[0007] To overcome the above-mentioned and other problems in the prior art, a high surface area porous silicon substrate material for forming an anode electrode of a lithium-ion secondary battery is provided. More specifically, according to the present disclosure, the silicon substrate material is subjected to electrochemical etching to form interconnected nanostructures or through-holes or pores through the silicon substrate material. Then, an electrochemically active material such as a metal silicide is formed on the surface of the pores of the silicon substrate material, for example, by depositing a suitable metal, such as titanium or tungsten, on the porous silicon substrate material using various deposition techniques, including but not limited to chemical vapor deposition (CVD), plasma enhanced chemical vapor deposition (PECVD), thermal CVD, electroplating, electroless plating and / or solution deposition techniques, and the metal coating on the porous silicon substrate is converted to the corresponding metal silicide by heating.

[0008] The resulting substrate is a porous silicon substrate comprising a metallurgically bonded surface layer of metal silicide on the walls of the porous structure, which can be advantageously used as an electrode in a lithium ion secondary battery.

[0009] Although the resulting porous substrate material may be somewhat less efficient per charge volume than, for example, prior art carbon or graphite-based electrodes used in lithium-ion secondary batteries, the porous structure provides several important advantages. For one thing, the porous structure allows protons more time to travel within the electrode matrix. As a result, swelling during charging cycles is significantly reduced. This makes the substrate less likely to form dendrites or shatter during charging cycles. Thus, charging and discharging rates can be increased without the risk of shattering or explosion. Furthermore, when used as an anode, the anode can be made significantly larger than the cathode, which can further improve overall performance.

[0010] The present disclosure also provides a lithium ion battery comprising a cathode electrode, an anode electrode formed of a porous silicon substrate with at least a portion of the surfaces of the pores of the porous silicon substrate coated with a metal silicide, a separator element disposed between the cathode and the anode, and an electrolyte. The silicon substrate may comprise monocrystalline silicon, polycrystalline silicon, or amorphous silicon. The aspect ratio of the length to diameter of the pores is preferably greater than 50:1, and the electrolyte is LiPF 2 in an organic solvent such as vinylene carbonate, 1,3-propane sultone, 2-propyl methane sulfate, cyclohexyl benzene, t-amyl benzene, or adiponitrile, to name a few. 6 or LiBF 4 It is preferred to include a conventional lithium salt electrolyte such as

[0011] In one embodiment, the metal silicide film is, for example, TiSi 2 , CoSi 2 and WSi 2 is selected from the group consisting of:

[0012] The present disclosure also provides an electrode for use in a lithium ion battery, the anode electrode comprising a substrate formed of porous silicon having pores at least partially coated at their surface areas with a metal silicide, the silicon substrate may comprise single crystal silicon, polycrystalline silicon or amorphous silicon, the pores have a length to diameter aspect ratio of greater than 50:1 and the metal silicide is, for example, TiSi 2 , CoSi 2 and WSi 2 It is preferably selected from the group consisting of:

[0013] Further features and advantages of the present disclosure will become apparent from the following detailed description when read in conjunction with the accompanying drawings, in which like numerals represent like parts and in which: [Brief description of the drawings]

[0014] [Figure 1]FIG. 1 is a schematic block diagram illustrating a process for manufacturing an electrode material according to one embodiment of the present disclosure. [Diagram 2] 1A and 1B are cross-sectional views of an electrode material at various stages of manufacture according to the present disclosure. [Diagram 3] FIG. 2 is a schematic block diagram of a process for producing an electrode material according to another embodiment of the present disclosure. [Figure 4] FIG. 2 is a schematic block diagram of yet another process for producing an electrode material according to the present disclosure. [Diagram 5] FIG. 2 is a cross-sectional view of a secondary battery manufactured according to the present disclosure. [Figure 6] FIG. 2 is a schematic block diagram of yet another process for producing an electrode material according to the present disclosure. [Figure 7] FIG. 1 is a cross-sectional view of a secondary battery according to the present disclosure. [Figure 8] FIG. 1 is a perspective view of a battery manufactured according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] 1, starting with a thin single crystal silicon wafer 10, typically 50-200 mils thick, in an electrochemical etching step 12, the wafer 10 is electrochemically etched by applying a uniform electric field across the wafer while immersing the wafer in a dimethylformamide (DMF) / dimethylsulfoxide (DMSO) / HF etchant in an electrochemical immersion cell to form micron-sized through-holes or pores 16 through the wafer, as shown in FIG. 2A. The growth of well-defined cylindrical pores or through-holes can be controlled by controlling the etching conditions, i.e., etching current density, etchant concentration, temperature, silicon doping, etc., following the teachings of "Electrochemically Stable Silicon Wafers," vol. 13, no. 1, the contents of which are incorporated herein by reference.

[0016] The resulting pores have a high aspect ratio of length to cross-sectional diameter, typically exceeding 50:1. The resulting structure, shown in FIG. 2A, includes a porous silicon wafer 18 having substantially cylindrical through holes or pores 16, e.g., 180 μm long and 1.6 μm in diameter, i.e., an aspect ratio of 112.5:1, which is highly useful for use as electrodes in lithium-ion batteries, as described below. The walls of the porous silicon wafer 18 are then coated with a metal, such as titanium or tungsten, in step 20, and the metal-coated porous silicon wafer is then subjected to a heat treatment in a heating step 22, which converts the deposited metal in the heat treatment step 22 into the corresponding metal silicide 25. The result is a porous silicon substrate material 24, in which the walls of the pores of the material are coated with a thin layer of metal silicide material 26 (FIG. 2A).

[0017] FIG. 3 illustrates another embodiment of the present disclosure. The process begins with a silicon wafer 30, and in step 34, a thin metal layer 32 is applied to the backside of the wafer 30, for example by sputtering. The metal layer 32 on the backside of the wafer allows for better electrical contact to the wafer. Electrochemical etching (step 36) is used to form pores 37 through the silicon wafer 30. After the porous silicon is formed, a wet etch (step 38) is used to remove the thin metal layer 32 from the backside. Next, in step 40, a porous silicon wafer similar to the porous silicon substrate shown in FIG. 2A is coated with metal, and the metal is converted to silicide in a heating step 42 similar to the first embodiment. The result is a porous silicon substrate with the pore wall surfaces coated with metal silicide, similar to the porous silicon substrate shown in FIG. 2B.

[0018] 4 illustrates a third embodiment of the present disclosure. The process begins at step 52 by covering one side of a silicon wafer 50 with a sacrificial metal layer 54 formed of a noble metal, such as platinum. The wafer is then etched at step 56 using HF and H 2 O 2The silicon wafer 50 is electrochemically etched by applying a uniform electric field to the metal layer 54 and substrate wafer 50 while immersed in an electrochemical cell containing an etchant such as ethylene glycol, thereby producing substantially uniform pores 58 through the exposed portions of the silicon wafer substrate 50 to the metal layer 54. As above, the growth of well-defined cylindrical pores or through-holes can be controlled by controlling the etching conditions, i.e., etching current density, etching concentration, temperature, silicon doping, etc., again according to the teachings of Santos et al. Alternatively, the formation of pores or through-holes can be controlled by covering selected portions of the silicon wafer with a nanoporous anodic alumina mask. Self-assembled nanoporous anodic alumina is essentially an alumina-based nanoporous matrix characterized by a closed packed array of hexagonally arranged cells in the center of which cylindrical nanopores grow perpendicular to the underlying aluminum substrate. Nanoporous anodic alumina can be produced by electrochemical anodization of aluminum, again according to the teachings of Santos et al., which are incorporated herein by reference. The sacrificial metal layer 54 may then be removed, step 58, leaving a porous silicon wafer having substantially cylindrical through-holes or pores with a length to diameter aspect ratio of greater than 50:1, similar to the porous silicon substrate shown in Figure 2A. The porous silicon substrate is then coated with a metal, step 58, and heated, step 60, to convert the metal to a metal silicide, thereby producing a porous silicon substrate with the pore walls coated with a metal silicide, similar to Figure 2B.

[0019] The porous silicon wafers produced as described above are incorporated into lithium ion batteries as described below.

[0020] 5 shows a lithium-ion battery 60 according to the present disclosure. Battery 60 includes a case 62, an anode 64 formed of a porous silicon substrate coated with a metal silicide formed as described above, and a cathode 66 formed of graphite or the like, separated by a membrane or separator 68. Anode 64 and cathode 66 are connected to external tabs 70, 72, respectively. A lithium-containing electrolyte 74, for example lithium cobalt oxide, is contained within battery 60.

[0021] Both the anode and cathode allow lithium ions to enter and exit their structures through processes called intercalation and deintercalation, respectively. During discharge, positive lithium ions migrate from the negative electrode (anode) to the positive electrode (cathode), forming lithium compounds through the electrolyte, while the electrodes flow in the same direction through an external circuit. When the cell is charged, the reverse occurs, with the lithium ions and electrode migrating back to the negative electrode, at a net higher energy stake.

[0022] The configurations and advantages of the present disclosure are that the anode can be physically larger or thicker than the cathode. The thicker porous structure of the anode allows more time for protons to travel through the electrode matrix. Also, less lithium electrolyte is needed for similar energy storage. And, because protons migrate more slowly to the anode, it allows for faster charge and discharge rates without the risk of fracturing or crushing the electrode.

[0023] Modifications may be made in the above disclosure without departing from the spirit and scope thereof. For example, although the fabrication of the anode has been described as being formed from a single crystal silicon wafer, single crystal silicon ribbon may be advantageously employed to form the anode. With reference to FIG. 6, a silicon ribbon 80 may be employed in which the ribbon is passed through an electrochemical etching bath 82 to form pores in the ribbon, from there through a metallization station 84, and then through a heat treatment station 86 in a succession of steps to form metal silicides on the surfaces of the walls of the pores. The resulting porous silicon metal silicide coated ribbon may then be used to form lithium ion batteries by standard roll fabrication techniques. For example, with reference to FIG. 7, a silicide coated porous silicon ribbon anode electrode 84 may be assembled in a stack with a cathode electrode 86 between separator sheets 88. The electrodes 84, 86 and separator sheets 88 are rolled together into a jelly roll and then inserted into a case 90 having positive and negative tabs 92, 94 extending from the jelly roll. Tabs can then be welded to the exposed portions of electrodes 84, 86, the case 90 filled with electrolyte, and the case 90 sealed. The result is a high capacity lithium ion secondary battery whose anode material comprises a porous metal silicide coated porous silicon ribbon that can be repeatedly charged and discharged without adverse effects.

[0024] Still other modifications are possible. For example, rather than using single crystal silicon chips or ribbons, the silicon may be polysilicon or amorphous silicon. Also, while tungsten, cobalt, and titanium have been described as preferred metals for forming the metal silicide, other metals advantageously used in conventional formation may be employed, such as silver (Ag), aluminum (Al), gold (Au), palladium (Pd), platinum (Pt), Zn, Cd, Hg, B, Ga, In, Th, C, Si, Ge, Sn, Pb, As, Sb, Bi, Se, and Te. Also, LiPF 6 and LiBf 4While we have described LiCoO as a useful electrolyte, other electrolytes conventionally used in lithium-ion batteries include, but are not limited to, lithium cobalt oxide (LiCoO 2 ).

Claims

1. Cathode electrode an anode electrode formed of a porous silicon substrate having a large number of through holes formed therein, each of which has an aspect ratio of length to diameter of more than 50:1, wherein at least a portion of the surface of the through holes is covered with a metal silicide thin film without blocking the through holes; a separator element disposed between the cathode electrode and the anode electrode; and an electrolyte.

2. 10. The lithium ion battery of claim 1 , wherein the porous silicon substrate comprises single crystal silicon.

3. 10. The lithium ion battery of claim 1, wherein the porous silicon substrate comprises polycrystalline silicon.

4. 10. The lithium ion battery of claim 1 , wherein the porous silicon substrate comprises amorphous silicon.

5. 2. The lithium ion battery of claim 1, wherein the metal suicide thin film is selected from the group consisting of TiSi2, CoSi2, and WSi2.

6. The electrolyte is selected from LiPF6, LiBF4; 2. The lithium ion battery of claim 1.

7. An electrode for a lithium ion battery, comprising an anode electrode comprising a porous silicon substrate formed of porous silicon having a large number of through holes formed therein, the through holes having an aspect ratio of length to diameter of more than 50:1, and at least a portion of a surface of the through holes being covered with a metal silicide thin film without blocking the through holes.

8. 8. The electrode for a lithium ion battery of claim 7, wherein the porous silicon substrate comprises single crystal silicon.

9. 8. The electrode for a lithium ion battery of claim 7, wherein the porous silicon substrate comprises polycrystalline silicon.

10. 8. The electrode for a lithium ion battery of claim 7, wherein the porous silicon substrate comprises amorphous silicon.

11. 8. The electrode for a lithium ion battery of claim 7, wherein the metal silicide thin film is selected from the group consisting of TiSi2, CoSi2, and WSi2.

Citation Information

Patent Citations

  • Lithium-ion battery porous silicon film negative electrode structure and preparation method thereof

    CN111509216A

  • Method of manufacturing porous silicon

    JP2010251647A

  • Anode battery materials and methods of making the same

    JP2017152385A

  • Porous silicon anodes for rechargeable metal halide batteries.

    JP2023506683A

  • Template electrode structures for depositing active materials

    US8257866B2